Playing against empire. (3rd July 2018) - Cooper, Elizabeth
ABSTRACT: This paper uses the concept of mimicry to explore the ways in which the tensions of empire were 'played out' through the West India Regiments' performance of military music and cricket. Both tools and products of the British Empire, cricket and military music could be used at cross-purposes and gained meaning and ideological significance in practice. Attention to the cultural practices of the West India Regiments sheds significant light on the connections between early twentieth-century social change and the dynamics of nineteenth-century colonialism. Moreover, it opens up new – and possibly counterintuitive – connections between Caribbean military history and scholarship on the social and cultural forces that have shaped Caribbean society.